Accidents, liability obligations and monopolized markets for spare parts: profits and social welfare - Pio Baake (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze the effects of accidents and liability obligations on the incentives of car manufacturers to monopolize the markets for their spare parts. We show that monopolized markets for spare parts lead to higher overall expenditures for consumers. Furthermore, while the manufacturers invest more in order to offer cars with higher qualities, monopolization tends to reduce social welfare. Key for these results is the observation that high prices for spare parts entail a negative external effect inasmuch as liability obligations imply that consumers of competing products have to pay the high prices as well.
Keywords: L13; L42; D43; 330; aftermarkets; monopolization; liability; Kraftfahrzeugteil; Markt; Monopol; Produktqualität; Straßenverkehrsunfall; Haftung; Wohlfahrtseffekt; Theorie